2007
DOI: 10.1111/j.1365-2621.2006.01299.x
|View full text |Cite
|
Sign up to set email alerts
|

Fruit size and picking scar size in some blueberry commercial cultivars and hybrid plants grown in SW Spain

Abstract: Within a blueberry research program in SW Spain, five rabbiteye (Vaccinium ashei Reade) and nine southern highbush (Vaccinium corymbosum L.) commercial cultivars along with 38 hybrid plants, produced by crossing highbush and rabbiteye cultivars, were used. The differences in the fruit size and the picking scar size among the plants, and the annual differences within each plant were studied. No significant differences were found in the fruit length, width, weight and the picking scar size between the rabbiteye … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Firmness is one of the most important parameter of quality for blueberries produced for fresh market. Berry firmness affects fruit shelf life, and it is related to marketing, consumer acceptance and to post harvest decay of fruit (Donahue et al, 1999;Parra et al, 2007). Microclimatic conditions during harvest in protected plots seems not to affect this parameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firmness is one of the most important parameter of quality for blueberries produced for fresh market. Berry firmness affects fruit shelf life, and it is related to marketing, consumer acceptance and to post harvest decay of fruit (Donahue et al, 1999;Parra et al, 2007). Microclimatic conditions during harvest in protected plots seems not to affect this parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Results reflect that the main effect on fruit quality parameters measured was cultivar; production system did not explain much of the differences observed in the physico-chemical characteristics of fruits. Remberg et al (2006) reported quality differences among cultivars from American and European origin and Ballington et al (1984) concluded that, within a single location and year, genetic components are undoubtedly more important than environmental differences within the field. Variations in chemical composi-racteristics analyzed were not much affected by the use of a protected system production.…”
Section: Discussionmentioning
confidence: 99%
“…The picking scar size also affects blueberry commercialization, as bigger scars increase perishability and pathogen penetration (Parra et al, 2007). Among the associations detected for scar diameter, the most interesting was the SNP detected under a qvalue of 0.1, upstream of an auxin transporter 3, which controls cellular auxin influx.…”
Section: Biological Insights Into the Genetic Basis Of Fruit-related mentioning
confidence: 99%
“…The northern highbush blueberry cultivars ("Duke," "Bluecrop," "Goldtraube," and "Ozarkblue") were harvested in Sever do Vouga region (40 ∘ 30 fruits of each cultivar were weighed. The volume of these fruits was measured using a beaker with 100 mL of water.…”
Section: Sample Collectionmentioning
confidence: 99%